Experience of the implementation of Gender Policies in the Faculty of Social Sciences of the National University - Arias Cascante, Nalda (2020)
Abstract: The objective of this research was: to establish the impact of gender policies in the academic endeavor of the Faculty of Social Sciences. On the basis of the category of gender as a transdisciplinary theoretical perspective, to enrichment and visibility of methodological references open toward the understanding of the complex social reality, in the field of endeavor teacher.  The findings demonstrate the academic settings in which they have been imbued women in everyday life, permeated by the lingering effects of the patriarchal ideology; resulting in an androcentric culture that   stops the development opportunities in key of equality and equity for women academics. Also, the main results realize the need to promote the realization of in-depth studies and broad spectrum on the reality of women, on topics such as: inequity, inequality, bullying, discrimination, archetypes and apprehensions inaccurate.